The emerging role of m6A modification of non-coding RNA in gastrointestinal cancers: a comprehensive review - Wang, Meiqi; Liu, Zhuo; Fang, Xuedong; Cong, Xianling; Hu, Yue (Frontiers in Cell and Developmental Biology, 2023)
Gastrointestinal (GI) cancer is a series of malignant tumors with a high incidence globally. Although approaches for tumor diagnosis and therapy have advanced substantially, the mechanisms underlying the occurrence and progression of GI cancer are still unclear. Increasing evidence supports an important role for N6-methyladenosine (m6A) modification in many biological processes, including cancer-related processes via splicing, export, degradation, and translation of mRNAs. Under distinct cancer contexts, m6A regulators have different expression patterns and can regulate or be regulated by mRNAs and non-coding RNAs, especially long non-coding RNAs. The roles of m6A in cancer development have attracted increasing attention in epigenetics research. In this review, we synthesize progress in our understanding of m6A and its roles in GI cancer, especially esophageal, gastric, and colorectal cancers. Furthermore, we clarify the mechanism by which m6A contributes to GI cancer, providing a basis for the development of diagnostic, prognostic, and therapeutic targets.